2003
DOI: 10.1177/1087057102239665
|View full text |Cite
|
Sign up to set email alerts
|

Gα16/z Chimeras Efficiently Link a Wide Range of G Protein–Coupled Receptors to Calcium Mobilization

Abstract: G protein—coupled receptors (GPCRs) represent a class of important therapeutic targets for drug discovery. The integration of GPCRs into contemporary high-throughput functional assays is critically dependent on the presence of appropriate G proteins. Given that different GPCRs can discriminate against distinct G proteins, a universal G protein adapter is extremely desirable. In this report, the authors evaluated two highly promiscuous Gα16/zchimeras, 16z25 and 16z44, for their ability to translate GPCR activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…1). We have previously shown that the 16z44 chimera [17] exhibits robust coupling to numerous G i -coupled receptors [18]. Upon co-expression of CCR1 and 16z44, all chemokines except MIP-1ˇstimulated IP accumulation (Fig.…”
Section: Chemokines Differentially Regulate Couplingmentioning
confidence: 89%
“…1). We have previously shown that the 16z44 chimera [17] exhibits robust coupling to numerous G i -coupled receptors [18]. Upon co-expression of CCR1 and 16z44, all chemokines except MIP-1ˇstimulated IP accumulation (Fig.…”
Section: Chemokines Differentially Regulate Couplingmentioning
confidence: 89%
“…Because chemokine receptors including CXCR4 signal through the G i/o subfamily (28,29), we also used chimeras that were engineered to link G i/o -coupled receptors to Ca 2ϩ mobilization: chimera qi5 consisting of murine G␣ q with the 5 C-terminal amino acids changed from G␣ q to G␣ i2 (30) and chimera 16z44 consisting of human G␣ 16 and rat G␣ z (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…G protein signaling of the receptor chimeras was then examined by measuring [Ca 2ϩ ] i transients, which is an established tool to study activation of G proteins of the G q/11 subfamily or of chimeric G i/o -G q/11 G proteins (30,32). Stimulation of naive HEK293 cells with CXCL12 produced a subtle AMD3100-sensitive Ca 2ϩ signal (not shown), indicating that the cells expressed functional endogenous CXCR4 receptors.…”
Section: Regulation Of Ligand-independent Receptormentioning
confidence: 99%
“…1A 16 . The identity of the PTX-insensitive G protein is unlikely to be G q because DOR is incapable of interacting with G q (Liu et al, 2003).…”
Section: Stimulation Of Stat3mentioning
confidence: 99%